Clinical Translation of Self‐Assembled Cancer Nanomedicines. Issue 1 (28th September 2020) - Mi, Peng; Miyata, Kanjiro; Kataoka, Kazunori; Cabral, Horacio
Abstract: Nanomedicines are emerging as effective approaches for developing new strategies against cancer. Nanomedicines can be designed for selectively delivering probes and anticancer agents to tumors for achieving improved diagnostic or therapeutic efficacy, while relieving potential side effects. In particular, the number of formulations based on self‐assembled nanostructures under clinical evaluation is increasing due to their unique advantages for elegant and facile preparation, working at the biointerface and spatiotemporally controlling the function of drugs. Here, the current status of clinically used self‐assembled nanomedicines is presented, and recent advances of candidates in clinical trials are reviewed. In addition, the challenges and future prospects of nanomedicines in the clinic are discussed. Abstract : Self‐assembled nanomedicines prepared from bottom‐up approaches present advantageous features for clinical translation, including effective design manipulation by tailoring the forming molecules, and control of biological activity by engineering the structure. In this review, the current status of self‐assembled nanomedicines in preclinical and clinical stages is reviewed, particularly focusing on recent challenges faced in the clinic and perspectives on the future.